2015
DOI: 10.17265/2161-6256/2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Farm Location on Physiological Conditions and Productivity of Friesian-Holstein Crossbreed Cows

Abstract: Farm location is an important factor in dairy farms, as it is closely associated with temperature and humidity that are crucial factors of influencing the physiological conditions and productivity of cows especially during the lactation period. The purpose of this study was to determine the effect of farm location on the physiological conditions and productivity of cows. The study was involved in 18 lactating Friesian-Holstein crossbreed cows in three farmer groups, i.e., Nangkasawit, Plalangan and Sumurejo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In recent years, many scientists have been interested in modifying natural zeolites to improve their performance as catalysts in organic reactions by treating zeolites with acids (mostly H 2 SO 4 and HCl) and transition metals such as Fe and Cu [12][13][14][15]. In the case of Cu-modified zeolites, it has been reported that copper-containing zeolites show better results compared to other zeolites with different metal transitions in oxidative dehydrogenation of methanol [16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scientists have been interested in modifying natural zeolites to improve their performance as catalysts in organic reactions by treating zeolites with acids (mostly H 2 SO 4 and HCl) and transition metals such as Fe and Cu [12][13][14][15]. In the case of Cu-modified zeolites, it has been reported that copper-containing zeolites show better results compared to other zeolites with different metal transitions in oxidative dehydrogenation of methanol [16].…”
Section: Introductionmentioning
confidence: 99%